Pengaruh Kualitas Program Pelatihan, Dukungan Organisasi, dan Budaya Inovatif terhadap Peningkatan Kompetensi Peserta Diklat di Balai Pelatihan Teknik Traksi Darman Prasetyo PT KAI (Persero) - Oktavia Eka Nahayun; Didik Subiyanto; Tri Ratna Purnamarini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze how the quality of training programs, organizational support, and innovative culture contribute to improving the competence of trainees at BPTT Darman Prasetyo PT Kereta Api Indonesia (Persero). A quantitative approach was used, involving 97 respondents as research samples. The research instruments were first evaluated through validity and reliability tests to ensure the accuracy and consistency of the measurements. The next stage included a series of classical tests for normality, multicollinearity, and heteroscedasticity to ensure that the analysis model met the relevant statistical requirements. After all analyses were completed, linear multiple regression was applied to identify and measure the contribution of each variable to the improvement of participants' competencies. The results of the analysis show that organizational support has a positive and significant effect on strengthening competency. The quality of the training program and innovative culture also show a positive effect, but have not yet reached a level of significance in terms of competency. The findings of this study confirm that adequate organizational support is a dominant element in encouraging an increase in the competency of training participants.